Energy harvesting materials - Andrews, David L., 1952- (World Scientific Pub. Co., 2005)
The science of energy harvesting materials is experiencing phenomenal growth and attracting huge interest. Exploiting recently acquired insights into the fundamental mechanisms and principles of photosynthesis, it is now possible to forge entirely new and distinctive molecular materials and devise artificial photosystems and applications far remote from conventional solar cell technology. In this comprehensive treatment of energy harvesting, a team of internationally acclaimed scientists at the forefront of the subject paint a state-of-the-art picture of modern energy harvesting materials science. Covering all aspects of the subject, ranging from natural plant and bacterial photosystems, through their biologically inspired synthetic analogs, to other photoactive molecular materials such as dendrimers, the book also establishes the theory and underlying principles across the full range of light harvesting systems. This title has recently been updated with 8 Digitized Graphs covering excitation energy, free energy, energy transfer and other useful information. With an authoritative, comprehensive and well-referenced content, it will appeal to all students, researchers and technologists interested or involved in solar energy, photobiology and photoactive materials science.